Leptospira sp. infection in bats: A systematic review and meta‐analysis. Issue 5 (30th May 2022) - Esteves, Stephanie Bergmann; Gaeta, Natália Carrillo; Batista, Juliana Maria Nunes; Dias, Ricardo Augusto; Heinemann, Marcos Bryan
Abstract: Bats are the only flying mammalian animals and are distributed worldwide. Bats are well‐known hosts of several zoonotic viruses and bacteria, including Leptospira sp. Here, we performed a systematic review and a meta‐analysis of evidence of Leptospira sp. infection in bats by examining studies published between 1964 and 2021. We reported the frequencies of various species and serogroups on all continents, several species and feeding habits of bats, and different diagnostic tools. Together, 33 papers from all continents with seven to 2077 individuals from one to 31 species were included. Molecular detection was conducted in most studies, followed by MAT (Microscopic Agglutination Test) and isolation and identification. Molecular characterization of Leptospira sp. revealed L. borgpetersenii as the most frequent species. Moreover, 179 positive samples for MAT contained the most likely infecting serogroups described, particularly the Australis serogroup. The percentage of positive tests in isolation and identification ranged between 0% and 0.5%. The highest frequency of Leptospira infection among the continents was observed in Asia, whereas South America had the lowest percentage. Finally, Nycteridae and Rhinonycteridae were the most frequently infected bat families. Our study provides valuable information about the epidemiology of Leptospira sp. infection in bats.